Rekomendasi Tempat Wisata Di Kabupaten Grobogan - Laodikia Galih Krisna Perbawa; Muhammad Hasbi; Bebas Widada (STMIK Sinar Nusantara, 2021)
Geografis Information System (SIG) is a computer system used to manipulate geographic data. The system is implemented with computer hardware and software that serves to init and verify data, data compilation, data storage, data changes and updates, data management and exchange, data manipulation, data calling and presentation and data analysis.In Grobogan Regency itself there are still many tourist locations that are not known to the public, especially tourists outside the area. The number of tourist attractions in Grobogan Regency itself is approximately 21 places, both natural tourism such as Waterfalls, Sendang, Goa.Religious tourism such as Tombs or artificial tourism such as swimming pools and reservoirs.Because of the time and information, people find it difficult to know the point of location and also information from the tours located in Grobogan Regency. In this Thesis Study use the Haversine Formula Method. With analysis, system design, coding/construction, testing, and implementation. At the analysis stage, the collection of data is observation and literature studies. While the data source obtained in the form of primary data and secondary data. At the design stage of the system using Unified Modelling Language (UML) include use case diagrams, activity diagrams, sequence diagrams, and class diagrams. At the construction stage use google maps API, PHP and MySQL programming languages. And at the testing stage using the Blackbox technique. While the implementation of this system can be used on desktop devices. By using the search for the nearest route and can recommend it from a radius of 20 km.The expected result of this study is that the app can recommend tourist attractions based on distance and also include tourist information located in Grobogan, so that tourists can easily access the tourist attractions they want to go to.